The role of Snail1 transcription factor in colorectal cancer progression and metastasis - Brzozowa, Marlena; Michalski, Marek; Wyrobiec, Grzegorz; Piecuch, Adam; Dittfeld, Anna; Harabin-Słowińska, Marzena; Boroń, Dariusz; Wojnicz, Romuald (Contemporary Oncology/Współczesna Onkologia, 2015)
Snail1 is a zinc-finger transcription factor, which plays a role in colorectal cancer development by silencing E-cadherin expression and inducing epithelialmesenchymal transition (EMT). During EMT tumour cells acquire a mesenchymal phenotype that is responsible for their invasive activities. Consequently, Snail1 expression in colorectal cancer is usually associated with progression and metastasis. Some studies revealed that about 77% of colon cancer samples display Snail1 immunoreactivity both in activated fibroblasts and in carcinoma cells that have undergone EMT. Therefore, expression of this factor in the stroma may indicate how many cells possess the abilities to escape from the primary tumour mass, invade the basal lamina and colonise distant target organs. Blocking snail proteins activity has the potential to avert cancer cell metastasis by interfering with such cellular processes as remodelling of the actin cytoskeleton, migration and invasion, which are clearly associated with the aggressive phenotype of the disease. Moreover, the link between factors from the snail family and cancer stem cells suggests that inhibitory agents may also prove their potency as inhibitors of cancer recurrence.